Penyelesaian Perkara Melalui Asas Restorative Justice terhadap Pelaku Tindak Pidana dalam Tingkat Penuntutan oleh Jaksa Penuntut Umum - Dicky Yunandar Siregar (Lembaga Pengembangan Kinerja Dosen, 2024)
The implementation of the principles of Restorative Justice at the prosecution level by the Public Prosecutor aims to achieve more holistic and sustainable justice, taking into account the interests of all parties involved in criminal incidents. This approach places attention on recovery and reconciliation, while considering the goals of the perpetrator's rehabilitation and the victim's recovery. The aim of this research is to find out and understand the process of resolving the principles of restorative justice against perpetrators of criminal acts at the prosecution level by the public prosecutor and to find out the legal consequences of resolving cases using the principles of restorative justice in the prosecution process by the public prosecutor. The research method used in this research is normative juridical using a descriptive analysis approach. The data sources used are primary legal materials, secondary legal materials and tertiary legal materials. The data collection technique used in this research is Library Research (Library Study). The research results show that the process of resolving the principles of Restorative Justice for perpetrators of criminal acts at the prosecution level by the Public Prosecutor refers to a legal approach that focuses on recovery and reconciliation, by involving perpetrators, victims and the community in the process of resolving criminal cases. The legal consequences of resolving cases using the principles of restorative justice in the prosecution process by public prosecutors are carried out based on the principles of restorative justice by providing an impact that can create better solutions than traditional punishment approaches. Sanctions that are educational in nature, such as community service, educational programs, or rehabilitation, can provide opportunities for offenders to learn and grow from their experiences.